2008
DOI: 10.1063/1.3033407
|View full text |Cite
|
Sign up to set email alerts
|

Conformable coating of SiO2 on hydrothermally grown ZnO nanorods

Abstract: Coating silicon dioxide on hydrothermally grown ZnO nanorods is demonstrated using a low temperature plasma enhanced chemical vapor deposition (PECVD) system. Wurtzite structured ZnO nanorods were prepared by spin coating ZnO nanocrystals onto plastics or glass substrates. Then, the nanorods were subsequently grown in a zinc nitrate solution. SiO2 was deposited by PECVD at 50 °C. No current could be measured through the patterned metal dots on the SiO2 coated sample, which indicates that SiO2 was covered seaml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…1A, white arrows). Importantly, the SiO 2 coatings were deposited uniformly on each nanorod free of any local defects, which was confirmed with TEM, local electrical conductance measurements, chemical wet-etching and photoluminescence A intensity measurements [37]. Our technique thus resulted in randomly oriented, upright SiO 2 deposited nanorods that cover the surface with densely packed monolayers without any defects over cm length scales (Fig.…”
Section: Fabrication Of Sio 2 Coated Nanorodsmentioning
confidence: 78%
See 2 more Smart Citations
“…1A, white arrows). Importantly, the SiO 2 coatings were deposited uniformly on each nanorod free of any local defects, which was confirmed with TEM, local electrical conductance measurements, chemical wet-etching and photoluminescence A intensity measurements [37]. Our technique thus resulted in randomly oriented, upright SiO 2 deposited nanorods that cover the surface with densely packed monolayers without any defects over cm length scales (Fig.…”
Section: Fabrication Of Sio 2 Coated Nanorodsmentioning
confidence: 78%
“…To arrest the nanorod growth, the substrates were removed from solution, rinsed with de-ionized water and dried in air at room temperature. SiO 2 was deposited with a Unaxis 790 plasma enhanced chemical vapor deposition (PECVD) system at 50 C using N 2 O and 2% SiH 4 balanced by nitrogen as the precursors as reported before [37]. Patterned nanorods were fabricated by conventional photoresist (PR) lithography [36].…”
Section: Fabrication Of Nanorodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, however, there is little consistency regarding the consequences of such coatings, with different studies reporting enhanced ultraviolet (UV) band emission, enhanced visible-band emission, or unchanged emission intensities. [18][19][20][21] We have recently reported the fabrication of ZnO nanodot/ SiO 2 nanorod arrays by exposing thin (∼20-30 nm diameter) ZnO nanorods to a silica coating process. The thin nanorods evolve into ZnO nanodots during the coating process and the resultant composite ZnO nanodot/SiO 2 nanorods exhibit up to 2-fold enhanced UV emission efficiencies (along with a weak visible emission).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Previous studies have reported that SiO 2 -coated ZnO NRs display high sensitivity towards detecting ultraviolet (UV) photons 36 and biomolecules, 37 good UV-durable superhydrophobicity, 38 and enhanced UV emission. 39,40 Conversely, heterogeneous ZnO ND/SiO 2 structures reportedly show enhanced visible emission 41 but negative photoconductivity. 42 It may be relevant to note that in most such studies reported to date, the ZnO NDs were either embedded in bulk SiO 2 or individual silica-coated ZnO NDs were randomly distributed in solution.…”
Section: Introductionmentioning
confidence: 99%